Missense mutations in the gene encoding prothrombin corresponding to Arg596 cause antithrombin resistance and thrombomodulin resistance - Takagi, Yuki; Murata, Moe; Kozuka, Toshihiro; Nakata, Yukiko; Hasebe, Ryo; Tamura, Shogo; Takagi, Akira; Matsushita, Tadashi; Saito, Hidehiko; Kojima, Tetsuhito (Thrombosis and Haemostasis, 2016)
Antithrombin (AT) and thrombomodulin (TM) play important roles in the process of natural anticoagulation in vivo. Recently, we reported that the prothrombin Yukuhashi mutation (p.Arg596Leu) was associated with AT and TM resistance-related thrombophilia. To assess the AT and TM resistances associated with other missense mutations by single base substitution in the Arg596 codon, we generated recombinant variants (596Gln, 596Trp, 596Gly, and 596Pro) and investigated the effects on AT and TM anticoagulant functions. All variants except 596Pro were secreted in amounts comparable to that of the wild-type but exhibited variable procoagulant activities. After a 30-minute inactivation by AT, the relative residual activity of wild-type thrombin decreased to 15 ± 4.0%, in contrast to values of all variants were maintained at above 80%. The thrombin–AT complex formation, as determined by enzyme-linked immunosorbent assay, was reduced with all tested variants in the presence and absence of heparin. In the presence of soluble TM (sTM), the relative fibrinogen clotting activity of wild-type thrombin decreased to 16 ± 0.12%, whereas that of tested variants was 37%–56%. In a surface plasmon resonance assay, missense Arg596 mutations reduced thrombin–TM affinity to an extent similar to the reduction of fibrinogen clotting inhibition. In the presence of sTM or cultured endothelial-like cells, APC generation was enhanced differently by variant thrombins in a thrombin–TM affinity- dependent manner. These data indicate that prothrombin Arg596 missense mutations lead to AT and TM resistance in the variant thrombins and suggest that prothrombin Arg596 is important for AT- and TM- mediated anticoagulation.
Keywords: Prothrombin; missense variant; Arg596; antithrombin resistance; thrombomodulin resistance